Obrazy współczesnego polskiego rodzicielstwa na przykładzie użytkowników aplikacji Instagram - Gałązka, Natalia (Kultura-Społeczeństwo-Edukacja, 2023)
The aim of the article is an attempt to characterize the parenting images specific to Polish users of the Instagram application. The article is an analysis based on a review of scientific pedagogical literature and media studies, as well as on the results obtained from own analysis in the scope of the discussed subject area. The issue of new media (especially social media), their function and importance in human life and the impact on the perception and fulfillment of the role of a parent will be discussed. The concept of sharenting as one of the forms of presenting one’s parenthood in social media will also be introduced. The topic related to the concept of photo-everyday life and social exhibitionism in the virtual space will also be addressed in relation to the activity of parents on Instagram. The author’s typology will also be presented, including typical images of parenting, selected on the basis of the analysis of accounts of well-known public people who are active Instagram users.